Health impact of the Qali Warma school feeding program, Peruvian case: 2016 – 2019 - Pérez Ticse, Juan Carlos (2022)
The objective of the article is to evaluate the impact of the Qali Warma school feeding program on the nutritional status of children in Peru. Using the 2016-2019 Family Health Demographic Survey, nutrition, sociodemographic and health indicators were compared. An OLS regression model was fitted with fixed effects associated with nutritional status. The Qali Warma program achieved a reduction of anemia by 17.1%: high levels of mothers’ education, sufficient number of prenatal visits, growth controls and continuous participation in the program managed to reduce anemia significantly equally in all regions (Coast, Mountains, and Jungle).